2020
DOI: 10.48550/arxiv.2012.14507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cosmic-ray transport and gamma-ray emission in M31

Audrey Do,
Matthew Duong,
Alex McDaniel
et al.

Abstract: We study the possibility that an extended cosmic-ray leptonic and/or hadronic halo is at the origin of the large-scale gamma-ray emission detected from the Andromeda Galaxy (M31). We consider a broad ensemble of non-homogeneous diffusion scenarios and of cosmic-ray injection sources. We find that cosmic-ray electrons and protons could be, and very likely are, responsible for part, or all, of the gamma-ray emission from M31, including out to more than 100 kpc from the center of the galaxy. We also simulate poss… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…From the reconstructed angular intensity profile, we show that the M31 intensity profile can be fitted by a two-component parametrization made up by a Gaussian function, dominant within ∼ 0.3 • , and a power law at larger radii. The latter component could correspond to a superposition of several contributions such as the outer part of the disk, galactic bubbles similar to the ones of the Milky Way, and/or a large comic-ray halo surrounding M31 [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the reconstructed angular intensity profile, we show that the M31 intensity profile can be fitted by a two-component parametrization made up by a Gaussian function, dominant within ∼ 0.3 • , and a power law at larger radii. The latter component could correspond to a superposition of several contributions such as the outer part of the disk, galactic bubbles similar to the ones of the Milky Way, and/or a large comic-ray halo surrounding M31 [27].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies tested the extension of M31 in γ rays using various models for its morphology [2,12,23,25,26], mostly confirming the preference for a centrally concentrated emission. Additionally, [25] found weak evidence for the presence of "Fermi bubble"-like structures perpendicularly to M31's galactic plane, while [26,27] showed the existence of an extended excess up to 120 − 200 kpc (8 − 15 • ) away from the center of M31.…”
Section: Introductionmentioning
confidence: 99%
“…However, in larger galaxies, a significant gamma-ray background from the central regions of the halo has been detected. See, for instance, promising targets for DM searches such as the M31 (Andromeda) galaxy, where a central diffuse emission has been detected [5,25]; in other cases, the background source is genuinely a point-like object, such as an active galactic nucleus as in the case of M87 [26].…”
Section: Gamma-ray Backgroundmentioning
confidence: 99%
“…Dwarf spheroidal galaxies (dSphs) are of particular interest in indirect detection searches as they are generally DM-dominated and have a low astrophysical foreground [4]. Other prime targets are the Galactic center region and nearby galaxies such as M31 [5,6] and M87 [2,3,7].…”
Section: Introductionmentioning
confidence: 99%
“…It would imply the existence of a giant CR halo of radius ∼ 100 kpc surrounding Andromeda, and would require a non standard scenario for the transport of CRs into galactic halos. Remarkably, the existence of such large halos was proposed for both the MW and M31 (Feldmann et al 2013;Taylor et al 2014;Do et al 2020). In particular, it was shown that the interaction of CRs in the diluted circumgalactic gas around the MW could explain the diffuse flux of neutrinos revealed by Icecube (Taylor et al 2014), and a subdominant fraction of the isotropic gamma-ray background (Feldmann et al 2013).…”
Section: Introductionmentioning
confidence: 97%